Caribbean Report 08-06-1990 - Crosskill, Hugh (anchor); Fitzpatrick, Miles (interviewee); Martin, Lionel (correspondent); O'Connell, Rhona (analyst); Khan, Sharief (correspondent); Cezair, Percy (interviewee); Whitehorne, Pat (correspondent) (The British Broadcasting Corporation, 1990)
The Guyana Bar Association calls on the government to make amendments to the recently tabled Election Observers Bill in the Guyanese Parliament. Under the bill President Desmond Hoyte is empowered to invite observers for the country’s elections. The Bar Association is concerned that the bill does not clearly indicate that observers other than those invited by the President are welcomed and the element that it is a criminal offence to impersonate an observer. Secondly, a Soviet trade mission is in Cuba to work out the revised trading relations between the two countries. Cuba relies on the Soviet Union for 70% of international trade and this continued trade support from the Soviets is essential for the Cuban economy. Following the Financial News, the stand-off between the Surinamese army and the Jungle Commando in the bauxite mining town of Moengo continues. Ronnie Brunswick, leader of the Jungle Commando, threatened to blow up vital installations in the town of Moengo. The next segment covers Stories of Caribbean Interest in the British Press. The report concludes with Percy Cezair, Trinidadian Business Consultant and Journalist, agreeing with David Jessop, Head of the London-based West India Committee, that the Caribbean is suffering from the lack of an export culture.
1. Headlines (00:00-00:38)
2. The Guyana Bar Association is unhappy with two aspects of the Election Observers Bill now before Parliament. Comments from Miles Fitzpatrick, President of the Guyana Bar Association (00:39-03:37)
3. Soviet mission in Cuba to work out the new trading relations. Lionel Martin reports from Havana (03:38-06:12)
4. Financial News. Rhona O'Connell of Shearson, Lehman Hutton comments on the fall in the price of gold (06:13-07:54) (10:58-11:49)
Keywords: Elections -- Guyana.; Trade -- Cuba -- Soviet Union.; Bauxite -- Suriname.; Insurgency - Surinam -- Econimic aspects.; Trade -- Caribbean Area.; European Economic Community.; Jessop, David.; Guyana Bar Association.; Guyana Election Observers Bill.; Elections -- Observers -- Guyana.; Jungle Commando -- Suriname.